(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Effective collaboration between medical doctors and nurses is crucial for delivering high-quality patient care across various healthcare settings. This abstract explores case studies illustrating successful doctor-nurse collaboration in hospital emergency departments, surgical wards, and primary care clinics. In emergency departments, prompt communication and coordinated efforts between doctors and nurses lead to timely interventions and improved patient outcomes. Similarly, in surgical wards, thorough pre-operative planning, intraoperative support, and post-operative monitoring by both professionals contribute to enhanced patient safety and reduced complications. Moreover, in primary care clinics, collaborative efforts in patient assessment, treatment planning, and education facilitate comprehensive care for individuals with chronic conditions. These case studies underscore the significance of clear communication, mutual respect, and shared decision-making in fostering effective doctor-nurse collaboration, ultimately benefiting patient care and satisfaction.